Tuesday Blues and the day-of-the-week effect in stock returns - Chiah, Mardy; Zhong, Angel (Journal of Banking & Finance, 2021)
This study evaluates the impact of investor mood and mood contagion on the cross-section of Australian stock returns . While we document a day-of-the-week effect in Australia, there are noticeable differences to the US (Birru, 2018). Australian stock returns on Tuesday are significantly lower than other weekdays. This ‘Tuesday Blues’ effect is most prominent amongst speculative stocks which, being more difficult to value, are more likely to be influenced by investor mood. We further report that Australian speculative stock returns are more correlated with factors indicative of same-day domestic mood and lagged US mood. Exploiting the 14-hour difference in time zones, we find that Tuesday returns to Australian speculative stocks are lower following extremely negative Monday mood or high risk aversion in the US. Overall, our results are consistent with mood contagion across international markets, which contributes to the observed daily patterns in stock returns after recognizing differences in time zones.